2017
DOI: 10.1021/acs.molpharmaceut.7b00197
|View full text |Cite
|
Sign up to set email alerts
|

Chemical End Group Modified Diblock Copolymers Elucidate Anchor and Chain Mechanism of Membrane Stabilization

Abstract: Block copolymers can be synthesized in an array of architectures and compositions to yield diverse chemical properties. The triblock copolymer Poloxamer 188 (P188), the family archetype, consisting of a hydrophobic poly(propylene oxide) core flanked by hydrophilic poly(ethylene oxide) chains, can stabilize cellular membranes during stress. However, little is known regarding the molecular basis of membrane interaction by copolymers in living organisms. By leveraging diblock architectural design, discrete end-gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
74
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(89 citation statements)
references
References 36 publications
11
74
0
Order By: Relevance
“…A previous in-vivo study of membrane stabilization by block copolymers by Houang et al demonstrated that the replacement of a hydroxyl endgroup by a tert -butyl endgroup on the PPO block of a diblock analog to F68 could significantly enhance the stabilization efficacy of polymers on the dystrophic membrane. 58 This result also confirmed the importance of the endgroup, despite the fact that it is less significant in our case.…”
Section: Resultssupporting
confidence: 85%
“…A previous in-vivo study of membrane stabilization by block copolymers by Houang et al demonstrated that the replacement of a hydroxyl endgroup by a tert -butyl endgroup on the PPO block of a diblock analog to F68 could significantly enhance the stabilization efficacy of polymers on the dystrophic membrane. 58 This result also confirmed the importance of the endgroup, despite the fact that it is less significant in our case.…”
Section: Resultssupporting
confidence: 85%
“…The ability of PEO-PPO diblock copolymers to effectively protect damaged membranes from enzyme leakage in vitro demonstrates that the second hydrophilic PEO segment – present in triblock P188 – is not required for efficacy, in agreement with Houang, et al . 54 This result, and the impacts of composition and size, are consistent with a model in which the hydrophobic segment anchors the copolymer to the membrane while the hydrophilic segment interacts with the lipid head groups and the aqueous extracellular environment.…”
Section: Discussionsupporting
confidence: 86%
“…The membrane protection effects of varying copolymer size, composition, and architecture can be compared across the current myoblast LDH release assay and concurrent studies on liposomal integrity under free radical challenge 53 and maintenance of muscle torque in dystrophin-deficient (Dmd mdx ) mice under mechanical stress 54 . A slight protective efficacy of diblock E 75 P 16 m was also observed in mdx mice upon intraperitoneal injection though not upon subcutaneous injection, inverse of the result for triblock E 75 P 30 E 75 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that the copolymer inserted itself in the membrane, leading to the formation of hybrid membrane with better mechanical properties. Houang et al [170] compared the results obtained with MD simulations and with physiological studies. They used PEO-PPO copolymers with different PPO end groups and tested them as membrane stabilizer both in silico and in vitro.…”
Section: Computer-simulated Interactionsmentioning
confidence: 99%